Prognostic impact of body composition in hepatocellular carcinoma patients undergoing interventional and systemic therapy - Feng, Yun; Yu, Bingran; Liu, Anxiao; Cai, Chongpeng; Zhou, Changming; Tong, Tong; Wang, Lu; Pan, Qi (Frontiers in Nutrition, 2025)
BackgroundPrimary liver cancer, predominantly hepatocellular carcinoma (HCC), is a leading cause of cancer-related deaths globally. Despite advances in targeted therapy and immunotherapy, survival rates for advanced HCC remain low. Combining hepatic artery infusion chemotherapy (HAIC) with systemic therapies shows potential, but identifying patients who benefit most is challenging. Body composition, including sarcopenia and myosteatosis, has been linked to cancer prognosis, but its role in HCC patients receiving HAIC with targeted and immunotherapies is unclear.MethodsThis retrospective study analyzed 158 HCC patients treated with HAIC, tyrosine kinase inhibitors, and anti-PD-1 immunotherapy from January 2021 to October 2024. Body composition was assessed via CT scans at the L3 level, with sarcopenia defined by skeletal muscle index (SMI) and myosteatosis by skeletal muscle density (SMD). Progression-free survival (PFS) and overall survival (OS) were evaluated, and Cox regression analyses identified prognostic factors.ResultsSarcopenia cutoffs were 47.1 cm2/m2 (males) and 38.2 cm2/m2 (females); myosteatosis cutoffs were 40.8 HU (males) and 38.9 HU (females). Sarcopenic patients had lower BMI (p < 0.001) and higher ALBI scores (p = 0.006). Tumor response rates (ORR 53.4%, DCR 77.9%) were similar between sarcopenic and non-sarcopenic groups (p = 0.531 and p = 0.699). Myosteatosis showed no significant differences in ORR (54.0%) or DCR (77.0%) (p = 0.693 and p = 0.872). Median PFS did not differ between sarcopenic (9.53 months) and non-sarcopenic (13.87 months) patients (p = 0.536). However, sarcopenic patients had significantly shorter OS (20.80 vs. 35.97 months, p = 0.005). Myosteatosis also correlated with shorter OS (20.80 vs. 35.97 months, p = 0.021). Multivariate analysis identified sarcopenia as an independent risk factor for OS (HR: 0.527, p = 0.017), alongside AFP levels and tumor number.ConclusionSarcopenia and myosteatosis predict poor prognosis in HCC patients receiving HAIC with targeted therapy and immunotherapy. Sarcopenia is an independent risk factor for OS, highlighting the importance of body composition in prognosis. No significant associations were found between body composition and tumor response or PFS.